Development of the Instrument for the Measurement of Job Satisfaction of Employees Empirical Research at the University of Zagreb - Dražić Lutilsky, Ivana; Pološki Volić, Nina; Galić, Zvonimir (Oeconomica Jadertina, 2017)
Employees are the key to the success of any profit and non-profit organizations, and because of that, it was essential to develop an instrument for the measurement of job satisfaction of employees at the University of Zagreb. The quality of teachers is an important dimension of satisfaction with higher education among students. Without professional, motivated and enthusiastic teachers and teachers satisfied with their work, outputs of the higher education system are questionable. The purpose of this paper is to show the development of such a measurement instrument and to show the results of the conducted empirical research, which tested job satisfaction of employees at Higher Education Institutions (HEI) at the University of Zagreb (Croatia). The research was conducted in 2013 on four faculties. The research was conducted as part of a project focused on the development of integrated reporting for HEI, which also included the measurement of the satisfaction of students, financial indicators and the development of business processes, with the aim to show the usefulness of data provided by those instruments in relation to the improvement of educational processes of HEI. The research results indicate that employees of the University of Zagreb are overall satisfied with their jobs.
Keywords: integrated reporting; performance measurement; indicators; employees; University